1981
DOI: 10.1007/bf02497190
|View full text |Cite
|
Sign up to set email alerts
|

Janssen's problem

Abstract: 1. Consider a vessel filled with liquid. The problem of finding the pressure of the liquid on the bottom and sides of the vessel has an elementary solution. This solution follows from the equations of equilibrium, Pascal's law, and the absence of tangential stresses at the boundary. Now suppose that the vessel is filled with an ideally loose material consisting of separate solid particles. In this case the problem of determining the pressure is much more difficult. This is because there is no analog of Pascal'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The further research in this sphere is expected to enlarge the issues under considerations, on the one hand, [6,7], and to state problems more precisely in view of non-elastic behavior of medium, its possible unloading, on the other hand [8][9][10]. The continual approach to the problem doesn't require any hypotheses of an engineering scheme (such hypotheses are known to be quite approximate).…”
Section: Introductionmentioning
confidence: 99%
“…The further research in this sphere is expected to enlarge the issues under considerations, on the one hand, [6,7], and to state problems more precisely in view of non-elastic behavior of medium, its possible unloading, on the other hand [8][9][10]. The continual approach to the problem doesn't require any hypotheses of an engineering scheme (such hypotheses are known to be quite approximate).…”
Section: Introductionmentioning
confidence: 99%
“…Through his mathematical derivation and experiments on corn, silo design is greatly improved owing to his pioneered work which has laid the foundations for understanding of the behavior of a static granular system confined by silo walls. A review of his original paper can be found in many literatures elsewhere (2,3) .…”
Section: Introductionmentioning
confidence: 99%